Optimizing the Use of Used Materials for Hydroponic Growing Media in Community Empowerment and Environmental Management Efforts - Dinda Nor Rohmah; Naila Faza; Sri Wulandari; Zuhrotun Nafis A (Universitas Kristen Indonesia Toraja, 2024)
This article aims to examine the potential for optimizing the use of used materials for hydroponic planting media, focusing on two main aspects: community empowerment and environmental management. By utilizing used materials, it is expected to reduce dependence on limited natural resources, reduce agricultural production costs, and reduce the environmental impact of waste. In addition, the application of this technology can provide economic and social benefits to local communities, strengthening their capacity to maating these practices as part of a sustainable development strategy